Rubiaceae Juss. da restinga da APA de Algodoal/Maiandeua, Maracanã, Pará, Brasil - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2009)
Rubiaceae is represented in the Ambiental Preservation Area (APA) of Algodoal/Maiandeua by 17 species, distributed over 15 genera. The tribes with most species were Gardenieae, with four species and Spermacoceae, with three. Guettarda and Psychotria contain two species each, and the other genera one. Three species of Rubiaceae from the restinga were sinonimized, Alibertia myrciifolia Spruce ex K. Schum. (= Cordiera myrciifolia (Spruce ex K. Schum.) C. Persson & Delprete), Psychotria barbiflora DC. (= P. hoffmannseggiana (Willd. ex Roem. & Schult.) Müll. Arg.) e Tocoyena sprucei Standl. (= T. brasiliensis Mart.). The species of Rubiaceae are more concentrated in the Myrtaceae forest, diminishing, in number of species, in direction to the beach. Guettarda spruceana Müll. Arg., Oldenlandia tenuis K. Schum., Posoqueria latifolia (Rudge) Roem. & Schult. and Retiniphyllum schomburgkii (Benth.) Müll. Arg. are new records for the APA of Algodoal/Maiandeua.
Rubiaceae Juss. of the restinga from APA of Algodoal/Maiandeua, Maracanã, Pará, Brazil
Keywords: Taxonomia.; Florística.; Vegetação litorânea.; Estado do Pará.; Taxonomy.; Floristic.; Littoral vegetation.; Pará State.; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA